HEMATOLOGICAL PROFILE OF COVID-19 POSITIVE PATIENTS IN QUETTA, PAKISTAN - Salma Khalid; Muhammad Zahid Mustafa; Irfan Shahzad Sheikh; Zunera Tanveer; Habib Ur Rehman; Abdul Samad; Muhammad Shafee (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
In this study, the clinical symptoms and hematological variations of COVID-19 patients were assessed on the first day of examination. The patients were grouped on the basis of their admission to the Intensive Care Units (ICU) "Severe," High Dependency Units (HDU) "Moderate," or General Ward (Mild) of Fatima Jinnah Hospital, Quetta, Balochistan. The levels of leucocytes, neutrophils, lymphocytes, erythrocytes, hemoglobin, hematocrit, mean cell volume and MCHC in the blood upon their first medical examination day were retrieved from medical records of first day laboratory tests. These parameters are good indicators to gauge the course of the disease, protection against further body deterioration, reducing morbidity and mortality. The results of hematological profile revealed that there was an increase in neutrophils in moderate (76.58±1.78%), severe (76.07±2.52%) and critical (82.35±1.39%) groups while there was a decrease in lymphocytes in moderate (16.31±1.43%), severe (17.21±2.11%) and critical (12.74±1.25%) groups. There was an elevation in WBCs level of severe (11.38±0.88/L) and critical class (12.00±0.79/L). However, there was decrease in the hemoglobin (12.50±0.34 g/dL), hematocrit (34.10±0.97%), MCH (26.03±0.61 pg) and MCHC (29.58±0.73 g/dL) level of critical class. All the above results were showing significant difference (p<0.05) with non-COVID group.